2020
DOI: 10.3390/biom10101395
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondria in Melanoma

Abstract: Drastically elevated glycolytic activity is a prominent metabolic feature of cancer cells. Until recently it was thought that tumor cells shift their entire energy production from oxidative phosphorylation (OXPHOS) to glycolysis. However, new evidence indicates that many cancer cells still have functional OXPHOS, despite their increased reliance on glycolysis. Growing pre-clinical and clinical evidence suggests that targeting mitochondrial metabolism has anti-cancer effects. Here, we analyzed mitochondrial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 86 publications
(138 reference statements)
0
28
0
Order By: Relevance
“…According to recent evidence, mitochondrial metabolism was upgraded from a simple bystander in the oncogenic process to a fundamental player in all the phases of the tumoral process including malignant transformation, tumor progression, and treatment efficiency [ 8 ]. The implication of mitochondria in melanoma development resides in the metabolic plasticity displayed by melanoma cells in the presence of different activators (AKT (protein kinase B), BRAF (v-raf murine sarcoma viral oncogene homolog B1), p14ARF, MYC, NRAS (neuroblastoma RAS viral oncogene homolog), phosphatidylinositol-4,5- bisphosphate 3 kinase catalytic subunit a (PIK3CA), and phosphatase and tensin homolog (PTEN)) [ 9 ], as follows: (i) BRAF-mutant melanomas exhibit a glycolytic phenotype that switches to oxidative phosphorylation (OXPHOS) in the presence of BRAF inhibitors; (ii) NRAS-mutant melanomas rely on aerobic glycolysis, and (iii) melanomas expressing peroxisome proliferator-activated receptor γ, coactivator 1α (PGC-1α) or PTEN present enhanced OXPHOS associated with a reduced glycolytic profile [ 6 , 10 , 11 , 12 ]. Moreover, melanoma cells proved to be highly adaptable in a metabolic manner, in response to different environmental conditions, as hypoxia or low extracellular glucose.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent evidence, mitochondrial metabolism was upgraded from a simple bystander in the oncogenic process to a fundamental player in all the phases of the tumoral process including malignant transformation, tumor progression, and treatment efficiency [ 8 ]. The implication of mitochondria in melanoma development resides in the metabolic plasticity displayed by melanoma cells in the presence of different activators (AKT (protein kinase B), BRAF (v-raf murine sarcoma viral oncogene homolog B1), p14ARF, MYC, NRAS (neuroblastoma RAS viral oncogene homolog), phosphatidylinositol-4,5- bisphosphate 3 kinase catalytic subunit a (PIK3CA), and phosphatase and tensin homolog (PTEN)) [ 9 ], as follows: (i) BRAF-mutant melanomas exhibit a glycolytic phenotype that switches to oxidative phosphorylation (OXPHOS) in the presence of BRAF inhibitors; (ii) NRAS-mutant melanomas rely on aerobic glycolysis, and (iii) melanomas expressing peroxisome proliferator-activated receptor γ, coactivator 1α (PGC-1α) or PTEN present enhanced OXPHOS associated with a reduced glycolytic profile [ 6 , 10 , 11 , 12 ]. Moreover, melanoma cells proved to be highly adaptable in a metabolic manner, in response to different environmental conditions, as hypoxia or low extracellular glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the historical assumption about aerobic glycolysis as the major cancer energy source, many tumors reprogram their metabolism increasing mitochondrial activity to properly respond to the newly energetic and anabolic needs imposed by several stressors like CIN/aneuploidy 28,29,77 . In the particular case of melanoma, although the consensus in the field also attributes to glycolysis a predominant metabolic role, mainly in a BRAFV600 context, emerging data shows that mitochondrial energy metabolism also coexists and could represent a promising therapeutic target 7880 . Interestingly, similar to respiratory ATP depletion mediated by TRMT61B loss, it has been shown that chemical inhibition of OXPHOS reduces tumor growth and metastasis 81,82 .…”
Section: Discussionmentioning
confidence: 99%
“…The melanoma cell lines A375 (BRAFV600E/NRASwt; Sigma Aldrich, Darmstadt, Germany), WM47 (BRAFV600E/NRASwt; Wistar Institute, Philadelphia, PA, USA), WM3000 (BRAFwt/NRASQ61R; Rockland Inc., Philadelphia, PA, USA), and WM3311 (BRAF/NRAS/NF1 wild-type; Wistar Institute, Philadelphia, PA, USA) were cultured as described previously [ 10 ] and used to establish human melanoma xenografts.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic flux profiling of a panel of melanoma cell lines and melanocytes revealed an elevated glycolytic rate in melanoma cells compared to melanocytes, but also functional tricarboxylic acid (TCA) cycle flux even under hypoxia, suggesting that energy production in melanoma cells is not exclusively glycolytic [ 8 ]. Moreover, we and others have shown that human melanomas exhibit a variable but distinct metabolic signature, as some patient-derived melanomas and melanoma cell lines expressed the classic Warburg phenotype, whereas others maintained significant, high levels of OXPHOS [ 9 , 10 , 11 , 12 , 13 ]. One explanation for the high OXPHOS activity of some melanomas might be the so-called “reverse Warburg effect”.…”
Section: Introductionmentioning
confidence: 99%